Farmers’ crop choice decisions: Trends and determinants in Nigeria and Uganda - Amare, Mulubrhan; Mavrotas, George; Edeh, Hyacinth O. (International Food Policy Research Institute, 2018)
This study investigates the determinants of farmers’ crop choice decisions, crop area diversification, and income diversification in Sub-Saharan Africa using nationally representative panel data for Nigeria and Uganda. We use both the shares of land and income of the major crop categories to measure farmers’ crop choice decisions.